DIRECTIONS FOR THE DEVELOPMENT OF THE INFORMATION PRODUCTS MARKET IN UZBEKISTAN BASED ON FOREIGN EXPERIENCE - Abdullaev, Abdulla (THE INNOVATION ECONOMY, 2026)
The article analyzes directions for developing Uzbekistan’s information products market based on foreign experience. Comparative analysis and case study methods applied: India, Estonia, Israel. India’s IT Park model implemented since 2019: 147 → 2 384 residents (+1 521%), exports 0.6 → 901 million (+150,067%). Based on Estonia’s experience, 100+ government services transferred online. Israel model: IT Startup School, 500+ startups, 100 million fund. In 2024, AI Readiness Index 70th place (+17), Global Innovation Index 70th place (+23). Directions: training (2030: 300 000), digital infrastructure, international cooperation, innovation ecosystem. Challenges: regional inequality (82% Tashkent), low e-ID coverage, no venture capital, talent shortage. Strategic goal: 5 billion exports by 2030, regional IT hub.